1)
y-2x=1
6x-y=7 y=6x-7
6x-7-2x=1
6x-2x=1+7
4x=8
x=8:4
x=2
y=6*2-7
y=5
2)
x+y=6 x=6-y
3x-5y=2
3(6-y)-5y=2
18-3y-5y=2
-8y=-16
y=-16:-8
y=2
x=6-2
x=4
3)
7x-3y=13
x-2y=5 x=5+2y
7(5+2y)-3y=13
35+14y-3y=13
11y=13-35
11y= -22
y=-22:11
y=-2
x=5+2*(-2)
x=9
4)
2x+y=12 y= 12-2x
7x-2y=31
7x-2(12-2x)=31
7x-24+4x=31
11x=31+24
11x=55
x=55:11
x=5
y=12-2*5
y=2
5)
4x-y=11 y=4x-11
6x-2y=13
6x-2(4x-11)=13
6x-8x+22=13
-2x=13-22
-2x=-9
x=-9:-2
x=4,5
y=4*4,5-11
y=18-11
y=7
6)
8y-x=4 x=-4+8y
2x-21y=2
2(-4+8y)-21y=2
-8+16y-21y=2
-5y=2+8
-5y=10
y=10:-5
y=-2
x=-4+8*-2
x=-20
Объяснение:
х=0 5-х=0
х=5
2. 3х=2х²
2х²-3х=0
х(2х-3)=0
х=0 2х-3=0
2х=3
х=1,5
3. х²-3=0
х²=3
х=±кореньиз3
4. -2х²+х-3=0
2х²-х+3=0
D=1-4×3×2=1-24=-23 <0 - корней нет
5. х²+3х-2=0
D=9+4×2=9+8=17
х1,2=(-3±кореньиз17)/2